Konsep Pendidikan Islam Menurut Q.S. Luqman Ayat 12-19 - Nurul Hidayat (Ta'allum: Jurnal Pendidikan Islam, 2016)
Al-Qur’an as the main source of ethical decision in Islam providessome models of teaching, especially for children. This paper focused on educational concepts in Islam based on story of Luqman al-Hakim. According to him, Islamic educational concepts consist of Islamic monotheism, worship, amar ma’ruf nahi mungkar, and akhlakul karimah.